About the reason of quarks confinement in the Yang - Mills field - A.N. Volobuev (Физика волновых процессов и радиотехнические системы, 2015)
On the basis of the analytical solution at the some approximation of the Yang - Mills field equations the proof of inevitable existence of the quarks confinement is received. It is shown, that as a result of components of the field nonlinear interaction on a way of a possible start of a quark from the hadron the configuration of the field as a potential barrier is formed. Physical consequences of inversely proportionality of the tensor-potential field components from the strong coupling constant are discussed.